Construction of porous Si/Ag@C anode for lithium-ion battery by recycling volatile deposition waste derived from refining silicon. (1st February 2023) - Li, Yan; Chen, Guangyu; Liu, Wenxin; zhang, Chentong; Huang, Liuqing; Luo, Xuetao
Graphical abstract: Highlights: The preparation mechanism of P-SiNPs/Ag@C was discussed in detail. Anode materials derived from deposited silicon waste toward LiBs. Electrochemical performance of P-SiNPs/Ag@C anode was investigated. Abstract: Owing to the rapid advancement of the photovoltaic industry, a lot of photovoltaic (PV) silicon waste will be generated. Thus, the recycling and reuse of waste silicon have become particularly important, both for environmental remediation and economic benefits. In this work, a special structure of porous Si nanoparticles embedded nano-Ag and coated carbon layer (P-SiNPs/Ag@C) was produced by silver-assisted chemical etching (Ag-ACE) the deposited silicon waste. The special porous structure and carbon layer coating can effectively address the volume expansion issues during charge/discharge. The intercalated Ag nanoparticles greatly reduced the transfer impedance and enhanced the electrical conductivity of the anode material. As a result, the novel-designed P-SiNPs/Ag@C anode can maintain a prominent reversible capacity (1521 mAh·g −1 at 0.2 A g −1 after 50 cycles) and outstanding rate performance (1099 mAh·g −1 at 2 A g −1 ). When the current density at 1 A g −1, the specific capacity still maintains at 706 mAh·g −1 over 300 cycles. The superiority of the prepared P-SiNPs/Ag@C structures was further confirmed by Comsol Multiphysics software. Impressively, the synthesis route provides a novel avenue for value-added utilization of residual silicon waste resources from EB refining silicon and the preparation of high-performance lithium battery silicon-based anode.